MANFAAT Indigofera Sp. DALAM BIDANG PERTANIAN DAN INDUSTRI - Suharlina, - (Pastura, 2014)
Indigofera    sp. is a leguminous plant which has varoius species, wide spread in tropical regions and adapted to a wide range of environmental condition. Indigofera sp. has many benefits in agricultural and industrial sector. It is widely used in agriculture as forage because its  high protein content, easily cultivated, high adaptability, and high biomass production (I. zollingeriana, I. hirsuta, I. pilosa, I. schimperi Syn,    I.    oblongifolia,    I.    spicata,    I. subulata Syn, and I. trita). Over the last 5 years Indigofera sp has been explored as forage feed for the goats. As cover crops, Indigofera is used to prevent erosion and nutrient leaching in the soil surface (I. hirsuta and I. Trita) and it is also used as green manure, mulch, erosion control and ornamental plants (I. australis). In industrial sector, Indigofera sp. widely used as dyes and traditional medicine. Indigofera is used as a natural dye (I. tinctoria) because it contains an excellent pigment called ‘indigo’ to dye silk material. Indigofera sp is also used as traditional medicine because it contains phytochemical substance which roles as antipyretic, laxative, diuretic, and useful against snakes attack, bees and insect bites. Using Indigofera    spp. as traditional medicine should be considered to avoid causing poisoning.
Keywords: forage, green manure, Indigofera sp., traditional medicines, natural dyes